MARINE UNMANNED IMPACT DRONE BOAT WITH ULTRASONIC ACCELERATOR - AFTANAZIV, IVAN; SHEVCHUK, LILIA; SVIDRAK, INGA; STROHAN, ORYSA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A description of the design scheme of a marine unmanned attack drone-boat with an ultrasonic accelerator is given. Its increase in speed at the final stage of reaching a target pre-selected by the operator is provided by an ultrasonic generator of high-frequency electromagnetic waves installed in the hull of the drone-boat, the emitters of which are placed on the hull below its waterline to irradiate the water in which the hull moves and disturb its cavitation.It was found that the use of an ultrasonic generator, which includes a high-frequency pulse generator with an electrical power source, an amplifier with a resonator, and an emitter of ultrasonic high-frequency electromagnetic waves, is optimal for disturbing cavitation in offshore water. The emitters are washed with onboard water and are arranged in a staggered pattern on the boat's hull and bottom below its waterline.         It has been proven that the disturbance of the cavitation field under the bottom of the moving hull of the boat in offshore water reduces the viscosity of water by 30-40%, thereby reducing the hydrodynamic resistance of water by moving solid bodies in it. It was found that lowering the hydrodynamic resistance of the water on board contributes to increasing the speed of the boat's hull from its cruising speed of 75-80 km/h in the final section of the approach to the target to 95-100 km/h.It is noted that increasing the boat's speed contributes to a proportional increase in the kinetic energy of its impact on a previously selected target, increasing the degree of damage and destruction caused to the target.        It is estimated that increasing the speed of the drone-boat by 25-30% guarantees a 25-26% reduction in the duration of its stay in the affected area and, accordingly, proportionally lowers the probability of it being hit by the enemy's automated small arms.It is recommended to choose the design scheme and structure of powerful typical devices for ultrasonic welding as an ultrasonic generator of ultrasonic pulsating electromagnetic wave radiation. Their cheap parts and assemblies are mass-produced by industrial enterprises.
Keywords: sea water; attack boat; unmanned drone; movement speed; onboard water; cavitation; generator; ultrasound; emitter